Prediction of Clinical Outcome in Endometrial Carcinoma Based on a 3-lncRNA Signature - Ding, Hongmei; Jiang, Fei; Deng, Lifeng; Wang, Juan; Wang, Ping; Ji, Mintao; Li, Jie; Shi, Weiqiang; Pei, Yufang; Li, Jiafu; Zhang, Yue; Zhang, Zengli; et al. (Frontiers in Cell and Developmental Biology, 2022)
In present study, we constructed a new lncRNA model to predict the prognosis of patients with Endometrial Carcinoma (EC). Univariate COX regression and LASSO model were selected to find the 8-independent prognostic lncRNAs for EC patient from TCGA. Furthermore, the risk score of the 3-lncRNAs signature for overall survival was identified as: CTD-2377D24.6 expression × 0.206+ RP4-616B8.5 × 0.341 + RP11-389G6.3 × 0.343 by multivariate Cox regression analysis. According to the median cut off value of this prognostic signature, patients were divided into low-risk and high-risk sets, and demonstrated that the low-risk set had a higher survival rate than that of the high-risk set. In addition, the 3-lncRNAs signature was closely linked with histological subtype and advanced clinical stage in EC patients. Moreover, our clinical samples also confirmed that RP4-616B8.5, RP11-389G6.3 and CTD-2377D24.6 levels were increased in tumor tissues by qRT-PCR and in situ hybridization. Intriguingly, the p-value of combined 3-lncRNAs was lower than that of each lncRNA, indicating that the 3-lncRNAs signature also showed higher performance in EC tissue than paracancerous. Functional analysis revealed that cortactin might be involved in the mechanism of 3-lncRNA signatures. These findings provide the first hint that a panel of lncRNAs, may play a critical role in the initiation and metastasis of EC, indicating a new signature for early diagnosis and therapeutic strategy of EC.